True Versus Spurious State Dependence in Firm Performance: The Case of West German Exports - Ulrich Kaiser; Hans Christian Kongsted (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper analyzes the persistence of firms' exporting behavior in a panel of West German manufacturing firms. Dynamic binary choice models allow us to distinguish between true and spurious state dependence in firm performance. Using random effects models as well as a recent fixed effect approach which imposes few restrictions on unobservables, we find robust evidence of state dependence in the current export status of firms. Unobserved permanent firm heterogeneity ("spurious state dependence") is found to be less important than suggested by earlier studies. The existence of true state dependence in exports has direct economic policy implications: if policy successfully turns non-exporters into exporters, the effect is likely to be lasting.
Keywords: D21; C23; 330; state dependence; export activity; dynamic binary choice models; Exportindustrie; Staatliche Einflussnahme; Deutschland